2016
DOI: 10.1007/s41024-016-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Case study of permeability-reducing admixture use in anti-flotation slabs: building in Brasilia, Brazil

Abstract: The time that the concrete must keep its properties, known as service life, it is an important design parameter for the performance of concrete structures. A porous concrete has a higher degree of water and aggressive permeability agents, which can cause deterioration of the reinforcement for mechanisms such as corrosion, besides not ensuring the watertightness, for example, on slabs under negative hydrostatic pressure (anti-flotation slabs). This type of slab has been used for the purpose of enabling or facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…It has been shown that CAs improve the mechanical properties of concrete when using contents of 3%, 5%, and 7% of the cement content, subjected to moisture, though the aforementioned percentages may be quite high for an addition. Silva et al report a successful case study of an anti‐flotation slab of reinforced concrete where CAs were used to ensure water tightness . CAs are efficient in more than blocking pores as they also possess the capability of withstanding hydrostatic conditions and the ability of sealing hairline cracks when activated by moisture .…”
Section: Autogenous and Nonencapsulated Autonomous Self‐healingmentioning
confidence: 99%
“…It has been shown that CAs improve the mechanical properties of concrete when using contents of 3%, 5%, and 7% of the cement content, subjected to moisture, though the aforementioned percentages may be quite high for an addition. Silva et al report a successful case study of an anti‐flotation slab of reinforced concrete where CAs were used to ensure water tightness . CAs are efficient in more than blocking pores as they also possess the capability of withstanding hydrostatic conditions and the ability of sealing hairline cracks when activated by moisture .…”
Section: Autogenous and Nonencapsulated Autonomous Self‐healingmentioning
confidence: 99%
“…Self-healing concrete with crystalline admixtures has been used in several projects worldwide in the last decades, such as in Brazil (122): an anti-floating slab (1200 m³ of concrete), a wave-type coverage (320 m³), or one slab in the building basement and the reform of football Stadium complex. In these cases, visual inspections reported no cracks in the hardened concrete.…”
Section: Large Scale Testsmentioning
confidence: 99%
“…Regarding the evaluation properties, there are no standards, and in full-scale constructions, self-healing has validated only visually (122,123). At laboratory and pilot conditions (104,105,125,127), some transport properties and mechanical tests have been validated.…”
Section: Maturity Level Of the Technologymentioning
confidence: 99%
“…Se entiende como durabilidad en el área de la construcción, a la capacidad que presentan los elementos constructivos de conservar sus atributos físicos en el tiempo sin que se presenten mantenimientos prematuros o intervenciones constructivas no previstas, dependiendo siempre y cuando de las características físico-mecánicas y atributos físicos de los elementos constructivos con relación a su uso y condiciones ambientales (Broto and Soria, 2005;Monjo and Maldonado, 2001;Silva et al, 2017). Sin embargo, los sistemas constructivos como la mampostería para fachada (ladrillos, bloques de tierra comprimida, bloques de concreto), mampostería para sobrecimiento (bloques de concreto) y muros de medianería se encuentran sometidos a agentes externos como la lluvia y el agua proveniente del terreno que afectan la estabilidad física y estructural de estos elementos como consecuencia de la presencia de humedad durante largos periodos de tiempo (Jiménez, 2005;Anastasopoulos, 2013;Tokimatsu, 2012;Adam and Agib, 2001); Por otro lado (Cañola et al, 2020) determinan que el contacto de los sistemas de mampostería con agentes externos como el agua lluvia y el agua contenida en el terreno, pueden afectar los diferentes componentes de los muros como los mampuestos y morteros debido a la formación de agentes salinos correspondientes a las eflorescencias; por otra parte (Tsukagoshi et al, 2012;Saija, 1995) determinan que aunque los elementos constructivos como los morteros presenten sistemas de impermeabilización como barreras físicas en poliuretano frente a los agentes externos como el agua, estos elementos con el paso del tiempo pierden sus características físicas y espesor, haciendo que los sustratos en mortero sean mas vulnerables a los procesos de degradación por la carbonatación y procesos de agrietamiento.…”
Section: Introductionunclassified